Protective associations of HDL with blood-brain barrier injury in multiple sclerosis patients - Fellows, Kelly; Uher, Tomas; Browne, Richard W; Weinstock-Guttman, Bianca; Horakova, Dana; Posova, Helena; Vaneckova, Manuela; Seidl, Zdenek; Krasensky, Jan; Tyblova, Michaela; Havrdova, Eva; Zivadinov, Robert; et al. (Journal of lipid research, 2015)
The purpose of this work was to investigate the associations of serum cholesterol and apolipoproteins with measures of blood-brain barrier (BBB) permeability and CNS inflammation following the first clinical demyelinating event. This study included 154 patients [67% female; age, 29.5 ± 8.2 years (mean ± SD)] enrolled in a multi-center study of interferon β1-a treatment following the first demyelinating event. Blood and cerebrospinal fluid (CSF) were obtained at screening prior to treatment. A comprehensive serum lipid profile and multiple surrogate markers of BBB breakdown and CNS immune activity were obtained. Higher levels of serum HDL cholesterol (HDL-C) and ApoA-I were associated with lower CSF total protein level, CSF albumin level, albumin quotient, and CSF IgG level (all P ≤ 0.001 for HDL-C and all P < 0.01 for ApoA-I). HDL-C was also associated with CSF CD80+ (P < 0.001) and with CSF CD80+CD19+ (P = 0.007) cell frequencies. Higher serum HDL is associated with lower levels of BBB injury and decreased CD80+ and CD80+CD19+ cell extravasation into the CSF. HDL may potentially inhibit the initiation and/or maintenance of pathogenic BBB injury following the first demyelinating event.
Keywords: longitudinální studie; Inflammation; Blood-Brain Barrier; roztroušená skleróza; high density lipoprotein; apolipoproteiny; zánět; mužské pohlaví; interferon beta; Adult; Demyelinating Diseases; Apolipoproteins; Multiple Sclerosis; Interferon-beta; ženské pohlaví; Nervous System Diseases; apolipoproteins; Humans; demyelinizační nemoci; biologické markery; HDL-cholesterol; nemoci nervového systému; Longitudinal Studies; dospělí; Biomarkers; hematoencefalická bariéra; Female; Cholesterol, HDL; clinically isolated syndrome; lidé; Male; cholesterol